ANALISIS PENGENDALIAN INTERN TERHADAP PENGELOLAAN PERSEDIAAN BARANG PADA CV. MUTIARA INARA - Rusmida J H Hutabarat; Shelly Farida Tobing (Universitas Tridinanti, 2021)
This study aims to determine how the application of internal control to inventory management in CV. Inara Pearl. The method used is qualitative, which is mostly a description of the results of interviews and documentation studies. The data obtained will be analyzed qualitatively and described descriptively and given a complete picture of the object under study based on data obtained from the warehouse section of CV. Pearl Inara and is based on a theoretical foundation.From the results of the study concluded that the internal control of inventory at CV. Mutiara Inara has been quite effective, where there is a separation of duties and related functions in receiving and releasing goods. As well as the monitoring of inventory which is carried out periodically by the company through checking.Keywords: Internal Control, Inventory Management, Effective